Increased arterial stiffness predict major adverse cardiovascular events in post-infarcted patients. Do parameters and methods matter?. (3rd October 2022) - Gaszner, B; Simor, T; Van Der Geest, R J; Farkas, N; Meiszterics, Z
Abstract: Introduction: According to recent 2021 ESC prevention guidelines arterial stiffness (aortic pulse wave velocity – PWV, augmentation index - Aix) predicts future major adverse cardiovascular events (MACE). Both parameters have a prognostic relevance, however due to the various technical approaches the level of high stiffness values show significant differences and resulting an argue against widespread use. Purpose: We evaluated the cut-off PWV and Aix values for MACE prediction using cardiac magnetic resonance imaging (CMR) and oscillometric methods for validating the prognostic value of high stiffness parameters in post-infarcted patients. Methods: CMR phase contrast imaging (Siemens Avanto, 1, 5 T CMR device) and an invasively validated oscillometric based Arteriograph (AG) method were compared in this 6 years follow-up study, including 49 patients suffered previous ST-elevation myocardial infarction (STEMI). Patients received follow-up for MACE comprising all-cause death, non-fatal MI, ischemic stroke, hospitalization for heart failure and coronary revascularization. Results: 49 patients (37 male, average age: 57±8 years) were investigated. An acceptable agreement and significant correlation (Spearman's rho: 0.332, p<0, 01) was found between AG and CMR derived PWV values. Bland Altman plot was created to test for methods' agreement. The bias showed that in general the mean difference between the two measures was 3.6 m/s (upper and lower limit of agreement: –0.2 and 7.5 m/s). The coefficient of variation was 43.9%. Totally 51 MACE events occurred during the 6 years follow-up period. Hospitalisation for coronary revascularisation (55%), all-cause death (15%), non-fatal MI (12%), heart failure (12%) exposed the majority of MACE events. Optimized PWV and Aix cut-off values for MACE prediction were calculated (PWVCMR: 6, 47 m/s; PWVAG: 9, 625 m/s; AixAG: 34, 22%) by receiver operating characteristic analysis (Figure 1). Kaplan-Meier analysis in all parameters showed a significantly lower event-free survival in case of high PWV and Aix values (Figure 2). Multivariate Cox regression analysis revealed PWV and Aix as a predictor of MACE (PWVCMR hazard ratio (HR): 1.31 (CI: 1.1–1.7), PWVAG HR: 1.24 (CI: 1.0–1.5), AixAG HR: 1, 043 (CI: 1, 01–1, 08), p<0, 05 respectively). Conclusions: Arterial stiffness, particularly elevated PWV predicts MACE in postinfarcted patients. Our study showed both CMR and oscillometric techniques are feasible for MACE prediction, however, adjusted cut-off values of PWV are recommended for different methods to improve individual risk stratification. All these findings emphasize the clinical relevance for the future measurement of arterial stiffness might contribute to improved risk stratification after MI, which is crucial for the assessment of prognosis and guidance of secondary prevention treatment. Funding Acknowledgement: Type of funding sources: None.